2017
DOI: 10.1371/journal.pntd.0005426
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome composition of Aedes aegypti is not critical for Wolbachia-mediated inhibition of dengue virus

Abstract: BackgroundDengue virus (DENV) is primarily vectored by the mosquito Aedes aegypti, and is estimated to cause 390 million human infections annually. A novel method for DENV control involves stable transinfection of Ae. aegypti with the common insect endosymbiont Wolbachia, which mediates an antiviral effect. However, the mechanism by which Wolbachia reduces the susceptibility of Ae. aegypti to DENV is not fully understood. In this study we assessed the potential of resident microbiota, which can play important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 46 publications
(72 reference statements)
3
32
0
Order By: Relevance
“…No major human pathogens transmitted by C. quinquefasciatus have been reported in Grenada, but the mosquito is capable of transmitting several arboviruses that occur in other Caribbean islands (e.g., WNV, St. Louis Encephalitis virus) or in neighboring mainland South American countries (e.g., Wuchereria bancrofti) [17]. The microbial composition of A. aegypti and C. quinquefasciatus mosquitoes has been previously studied [18,19,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. However, several arthropod-borne diseases that are endemic to the mainland Americas are not believed to be established in Caribbean islands (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…No major human pathogens transmitted by C. quinquefasciatus have been reported in Grenada, but the mosquito is capable of transmitting several arboviruses that occur in other Caribbean islands (e.g., WNV, St. Louis Encephalitis virus) or in neighboring mainland South American countries (e.g., Wuchereria bancrofti) [17]. The microbial composition of A. aegypti and C. quinquefasciatus mosquitoes has been previously studied [18,19,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. However, several arthropod-borne diseases that are endemic to the mainland Americas are not believed to be established in Caribbean islands (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a stable infection with Wolbachia in laboratory-reared mosquitoes (A. aegypti) had only few effects on the microbiome. Moreover, significant changes in the microbiome composition did not affect the dengue-virus-blocking phenotype caused by Wolbachia infection in this host [40]. However, analyses of A. aegypti transinfected with Wolbachia, released in the field in Brazil and Vietnam to inhibit the dengue virus, revealed that Wolbachia increases susceptibility of mosquitoes to dengue infection.…”
Section: Interactions Between the Endosymbiont Wolbachia And Other MImentioning
confidence: 78%
“…A good example of this is the Wolbachia-mediated inhibition of dengue virus. Under laboratory conditions it was indicated that the microbiome composition of the mosquito Aedes aegypti is not critical for inhibition [40]. However, when released into the wild, the picture became more complex.…”
Section: Box 3 the Importance Of Laboratory Versus Field Studiesmentioning
confidence: 99%
“…Such transfection applications require careful testing, as Wolbachia phenotypes are not always the same between species (Veneti et al, 2012). Also, Wolbachia can reduce the relative number of other potentially beneficial symbiotic bacteria (Audsley, Ye, & McGraw, 2017;Ye et al, 2017) and conversely, other microbiota can outcompete Wolbachia (Kondo, Shimada, & Fukatsu, 2005;Goto, Anbutsu, & Fukatsu, 2006;Hughes, Rivero, & Rasgon, 2014;Rossi et al, 2015). These competition dynamics within microbiomes (Brinker et al, 2019;Gurung et al, 2019) are an important consideration when releasing manipulated strains into the field, as is the fact that new microbes introduced via hosts may become permanent fixtures in their ecosystem.…”
Section: Microbiome Manipulationmentioning
confidence: 99%